Acceptability of Nose-to-Brain Drug Targeting in Context to Its Advances and Challenges - Semwal, Ravindra; Upadhyaya, Kumud; Semwal, Ruchi B.; Semwal, Deepak K. (Drug Delivery Letters, 2018)
Background: In spite of a tremendous development in the neuroscience, particularly in the area of drug delivery, only a few drugs have been marketed for central nervous system related disorders. Aim: The present work aims to comprehensively review the recent advancements in the nose to brain drug targeting and the challenges in its administration. Method: Most relevant and selected peer-reviewed articles based on nose to brain targeting were accessed from the various online scientific databases including PubMed, Scopus and Google Scholar. All these articles were thoroughly reviewed and their significant findings were described with further recommendation. Results: The nasal route for brain targeting can be considered as the most suitable one due to rapid drug absorption through the highly vascularised mucosa. Moreover, various properties such as easy administration, evasion of GIT and first-pass metabolism, non-invasive, better bioavailability, and fast action make this route highly acceptable. However, there are many factors which affect the brain targeting; these include drugs and formulation related factors. Hence, the particle size, shape, molecular weight, chemical form and solubility of the drugs as well as drug concentration, buffer capacity and viscosity of the formulation are equally important in the nose to brain targeting. Conclusion: The outcome of nasal route of drug targeting is not up to the mark due to rare studies on its efficacy, toxicity and clinical trials. Therefore, more advanced investigations are still required to make this unique method applicable for the betterment of mankind.
Keywords: toxicology